The evolution of hierarchically structured communication - Planer, Ronald J. (Frontiers in Psychology, 2023)
Human language sentences are standardly understood as exhibiting considerable hierarchical structure: they can and typically do contain parts that in turn contain parts, etc. In other words, sentences are thought to generally exhibit significant nested part-whole structure. As far as we can tell, this is not a feature of the gestural or vocal communication systems of our great ape relatives. So, one of the many challenges we face in providing a theory of human language evolution is to explain the evolution of hierarchically structured communication in our line. This article takes up that challenge. More specifically, I first present and motivate an account of hierarchical structure in language that departs significantly from the orthodox conception of such structure in linguistics and evolutionary discussions that draw on linguistic theory. On the account I propose, linguistic structure, including hierarchical structure, is treated as a special case of structured action. This account is rooted in the cognitive neuroscience of action, as opposed to (formal) linguistic theory. Among other things, such an account enables us to see how selection for enhanced capacities of act organization and act control in actors, and for act interpretation in observers, might have constructed the brain machinery necessary for the elaborate forms of hierarchically structured communication that we humans engage in. I flesh out this line of thought, emphasizing in particular the role of hominin technique and technology, and the social learning thereof, as evolutionary drivers of this brain machinery.